The Arab Spring: How soon will foreign investors return? - Paul Antony Barbour; Persephone Economou; Nathan M. Jensen; Daniel Villar (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
The Arab Spring dramatically increased investors' perceptions of political risk in MENA. An examination of these perceptions indicates long-run optimism that political transitions in the region – if democratic and coupled with political stability – could increase FDI and contribute to MENA's economic development.
Keywords: 330